Business System Long-Term Viability Across Life-Cycle Phases - Kremsar, Sara; Krhač Andrašec, Eva; Kern, Tomaž (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
This research addresses how business systems can achieve short-term success while sustaining long-term viability. Although the organizational literature already examines performance, resilience, and life-cycle dynamics, it lacks an integrated, empirically grounded framework that systematically connects internal and external factors to long-term viability across developmental phases. The research is conceptualized as a proposed Design Science Research study and will adopt a mixed-methods approach, combining qualitative and quantitative methods to identify, classify, and analyse factors influencing both short-term success and long-term viability. Using a five-phase life-cycle typology as an analytical framework, the research is expected to develop a reference model and accompanying analytical factor cards as its primary artefact. The original scientific contribution of the research is expected to lie in distinguishing short-term success from long-term viability, classifying factors across life-cycle phases and integrating them into a unified model. The results are expected to advance organizational theory and provide a structured analytical foundation for examining long-term viability in complex environments.